Role of the Rutin and Genistein Flavonoids in Soybean Resistance to Piezodorus guildinii (Hemiptera: Pentatomidae) - Bentivenha, Jose P. F.; Canassa, Vinicius F. [UNESP]; Baldin, Edson L. L. [UNESP]; Borguini, Milena G. [UNESP]; Lima, Giuseppina P. P. [UNESP]; Lourencao, Andre L. (Springer, 2018)
The stink bug complex includes some of the most important soybean pests worldwide. Among these insects, Piezodorus guildinii (Westwood) (Hemiptera: Pentatomidae) is known for the severe damage it can cause and for its resistance to chemical management. Host plant resistance is considered as an important tool in the management of these pests. In particular, plant flavonoids, such as genistein and rutin, have been identified as compounds that might negatively affect the development of some pests; however, the effects of these compounds on some stink bug species are still unclear. We tested the resistance of soybean genotypes by evaluating the growth and survival of P. guildinii under laboratory conditions. In addition, the amounts of genistein and rutin were quantified in both infested and non-infested genotypes. The PI 274453, PI 274454, PI 227687, PI 229358, 'IAC 100', and 'IAC 19' genotypes showed antibiosis to P. guildinii. The genistein and rutin flavonoids appear to play a role in the resistance of these genotypes against P. guildinii; specifically, PI 274453, PI 274454, and 'IAC 100' showed induced resistance against the insect. Other defence mechanisms or flavonoids might be involved in resistance in the L1-1-01 and PI 171451 genotypes. These results help us better understand the role of flavonoids in plant defence mechanisms and might prove useful in breeding programmes aimed at developing resistant soybean plants.
Keywords: Glycine max; Induced resistance; Flavonoid; Redbanded stink bug; Antibiosis